2015
DOI: 10.12750/jet.2015.30.4.271
|View full text |Cite
|
Sign up to set email alerts
|

Motility, Fertilizability and Subsequent Embryonic Development of Frozen-thawed Spermatozoa derived from Epididymis in Hanwoo

Abstract: The aim of the study was to investigate the ability of sperm derived from the epididymis in regard to sperm motility, sperm penetration to oocyte and subsequent development of the embryo. Frozen-thawed sperm from epididymis showed similar percentage of motile sperm (VSL ≥ 25 μm/sec) as compared to that of commercial sperm (control).Sperm penetration of frozen-thawed epididymal and commercial sperm was not significantly different. Moreover, cleavage and blastocyst rates were similar in both epididymal and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Because the catheter could extend from the uterine body to the deep uterine horn without damaging the inner uterine wall, this insemination method may improve the pregnancy rate without negatively impacting the uterine wall (Verberckmoes et al, 2004). In contrast to AI using epididymal spermatozoa in vivo, the fertilization rate of epididymal spermatozoa in vitro was similar to that of ejaculated spermatozoa when epidydimal spermatozoa and oocytes were co-incubated, as shown in our previous report (Yang et al, 2015). We speculated that, under such conditions in vitro, they formed a small droplet or well.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Because the catheter could extend from the uterine body to the deep uterine horn without damaging the inner uterine wall, this insemination method may improve the pregnancy rate without negatively impacting the uterine wall (Verberckmoes et al, 2004). In contrast to AI using epididymal spermatozoa in vivo, the fertilization rate of epididymal spermatozoa in vitro was similar to that of ejaculated spermatozoa when epidydimal spermatozoa and oocytes were co-incubated, as shown in our previous report (Yang et al, 2015). We speculated that, under such conditions in vitro, they formed a small droplet or well.…”
Section: Discussionsupporting
confidence: 53%
“…Epididymal spermatozoa in vitro do not consume energy moving to the isthmus of the uterus. Therefore, the in vitro fertilization rate of epididymal spermatozoa does not differ from that of ejaculated spermatozoa (Yang et al, 2015), despite epididymal spermatozoa showing low motility after incubation.…”
Section: Discussionmentioning
confidence: 90%
“…Epididymal spermatozoa can be stored for more than 24 h without loss of fertility [20]. Moreover, a recent study reported that epididymal spermatozoa had a similar fertilizing-capacity as fresh ejaculated spermatozoa using an in vitro fertilization system [21]. Therefore, the cryopreservation of epididymal sperm can be a useful assisted reproductive technology for the livestock industry and preserving genetic resources.…”
Section: Discussionmentioning
confidence: 99%
“…Spermatozoa motility was examined as previously described (Yang et al, 2015;Kang et al, 2016), with slight modifications. In brief, frozen semen was immersed in water at 37.5℃ for 40 s and mixed in a 1.5 mL tube.…”
Section: Spermatozoa Motility and Motility Parameters After Freezing-mentioning
confidence: 99%